Mindful strategies for helping college students manage stress : a guide for higher education professionals - Dye, Lacretia, 1975-; Burke, Monica Galloway; Mason, Cynthia Palmer, 1938- (New York, NY : Routledge, 2021)
"This practical resource offers a much-needed introduction to the why, what, and how of supporting college students through mindfulness and stress-releasing strategies. Higher education professionals are in a unique position to support, coach, and teach strategies with students to manage anxiety, emotional distress, and improve well-being. Drawing on experience from the disciplines of Mental Health, Counseling, and Student Affairs, the authors provide evidence-based practices and tangible techniques supported by the latest brain-based research and neuroscience. Full of tools that college students can use daily to assist with their relaxation meditation, focus, and stress management, this book helps higher education professionals who are not trained mental health practitioners to effectively and confidently incorporate activities to support the whole student"--
Mind, body, and spirit: community connection and relationships matter -- brain basics -- Relax and release -- A meditation a day -- Mindful movement -- Helping students with focus and choices for change -- Self-care is the new health care: prescriptions for well-being and being well.
OCLC-licensed vendor bibliographic record.
Keywords: College students -- Social conditions; College students -- Mental health; Stress management; Mindfulness (Psychology); Counseling in higher education; EDUCATION / Higher